2018
DOI: 10.1002/jcp.26397
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of porcine bronchoalveolar fluid‐derived mesenchymal stromal cells in a pig model of LPS‐induced ALI

Abstract: In this study, we isolated mesenchymal stromal (stem) cells (MSCs) from broncho-alveolar lavage fluid (BAL) of 2-6-week-old commercial pigs. BAL-MSCs displayed fibroblastic morphology and possessed self-renewal properties. Similar to bone-marrow MSCs, BAL-MSCs expressed mesenchymal markers and both cell types lacked the expression of hematopoetic markers. BAL-MSCs, when cultured in differentiation induction media, differentiated into adipocytes, osteocytes, and chondrocytes. Next, we examined if BAL-MSCs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…LPS can cause severe pneumonia and sepsis and activate the downstream nuclear factor-kappa B (NF-κB) signaling pathway producing inflammatory mediators [7,8]. LPS was widely used in preparation of ALI animal models [9][10][11][12]. Among pulmonary cells, vascular endothelial cells (ECs) perform the important barrier between intravascular (IV) and extravascular (EV), which are always the primary target of inflammatory agents in local or systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…LPS can cause severe pneumonia and sepsis and activate the downstream nuclear factor-kappa B (NF-κB) signaling pathway producing inflammatory mediators [7,8]. LPS was widely used in preparation of ALI animal models [9][10][11][12]. Among pulmonary cells, vascular endothelial cells (ECs) perform the important barrier between intravascular (IV) and extravascular (EV), which are always the primary target of inflammatory agents in local or systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we aimed to investigate whether miR-124-5p has biologic impacts on the alveolar epithelium, which may exert effects on the pathophysiology of ALI. Mesenchymal stem cells (MSCs) are a subset of cells with a variety of differentiation potential and previous studies have shown the benefits of MSCs-based therapy in respiratory injury [14]. Cell-free MSCs-conditioned medium (MSCs-CM) therapy has been demonstrated to confer pulmonary ischemic tolerance by paracrine factors, and we hypothesized that the administration of MSCs-CM would attenuate ALI through changing the delivery of miR-124-5p into epithelial cells, which will lead to the alteration in the protein expression of ENaC [15].…”
Section: Introductionmentioning
confidence: 99%
“…Acute lung injury (ALI) and its more severe form, acute respiratory distress syndrome (ARDS) with no effective treatment, are significant causes of morbidity and mortality in critically ill patients (Khatri & Richardson, 2018). Despite decades of tremendous research efforts, the mortality rate ranges from 22% to 40% (Xiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%